Women's attitudes toward menstruation : a quantitative survey and qualitative interview investigation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Fitzgerald, Bridget, M.A. (Massey University, 1990)
Menstruation plays an important role in the psychology of women. There is, however, little information about the nature of women's attitudes toward menstruation. The present study used a quantitative survey followed by a series of qualitative interviews to explore these attitudes in a sample of University women in New Zealand. The Menstrual Attitude Questionnaire (MAO) was used to assess the attitudes and beliefs of 343 women. The psychometric properties of the MAO and its underlying factor structure were examined using a range of factor analytic models. Responses were then used to select a sample of 1O women for interview. Interviews were conducted in order to elaborate upon the attitudes identified by the MAO and to examine in more depth the nature of women's attitudes toward menstruation. Factor analysis of the MAO yielded five orthogonal factors. Results suggested that these university women perceived menstruation as: Marginally causing physical, emotional and intellectual changes, a natural event, an inconvenience and slightly disrupting their usual performance and activities. Subjects accepted the existence of premenstrual tension. Similarly, interviews revealed that attitudes were multidimensional with each subject having an individual configuration of positive, negative and neutral beliefs about menstruation. No consistent pattern among the different beliefs was established. Furthermore, it would appear that attitudes towards menstruation may not be acquired from direct experience but may be learned through social expectations. Directions for future research are indicated, particularly the importance of qualitative research.
Keywords: Psychological aspects; Menstruation